Inflation and broadband revisited: Evidence from an OECD panel - Klaus S. Friesenbichler (Austrian Institute of Economic Research (WIFO), 2016)
This note revisits the conjecture that the use of broadband internet lowers transaction costs and thereby inflation. Using a macroeconomic panel of OECD countries, it roughly confirms previous findings reported by Yi and Choi (2005) by addressing conceptual and econometric issues.
Keywords: E31; O1; O3; 330; Inflation; broadband